On the status of Suifunema peregrinatum (Carreno, 2017) n. comb. (Nematoda: Oxyuridomorpha: Thelastomatidae) and first record of the species for Japan - Morffe, Jans; Carreno, Ramon A.; Ozawa, Sota; Sriwati, Rina; Hasegawa, Koichi (Zootaxa, 2019)
Blattophila peregrinata Carreno, 2017 (Nematoda: Oxyuridomorpha: Thelastomatidae) is proposed as a junior synonym of Suifunema peregrinatum (Carreno, 2017) n. comb., based on the revision of the type material of S. caudelli Chitwood, 1932, the type and only species of the genus. The revision permitted the emendation of some features of the original descriptions, namely the position of the nerve ring at level of the corpus instead the isthmus and the female genital tract didelphic-prodelphic instead didelphic-amphidelphic. The males of S. peregrinatum n. comb. are the only ones known for the genus. Thus, an amended generic diagnosis is given, including information on the males. Both S. peregrinatum n. comb. and S. caudelli differ by having a more slender body, a longer tail, and the vulva farther from the anterior end in the former. S. peregrinatum n. comb. is recorded for the first time from Pycnoscelus indicus Fabricius, 1775 (Blattodea: Blaberidae) from Japan. The specimens from Japan are morphologically consistent with other populations of the species from the USA and the Galapagos Islands of Ecuador. Only some morphometrics vary slightly, but these are within the range of the species. The phylogenetic position of the genus among the family Thelastomatidae is discussed, including sequences of the D2-D3 LSU rDNA of specimens from both the type population (Ohio, USA) and Japan.